Perinatal exposure to bisphenol A impacts in the mammary gland morphology of adult Mongolian gerbils - Leonel, Ellen Cristina Rivas [UNESP]; Campos, Silvana Gisele Pegorin; Bedolo, Carolina Marques Baraldi [UNESP]; Guerra, Luiz Henrique Alves [UNESP]; Vilamaior, Patrícia Simone Leite [UNESP]; Calmon, Marilia Freitas [UNESP]; Rahal, Paula [UNESP]; Amorim, Christiani Andrade; Taboga, Sebastião Roberto [UNESP] (Elsevier, 2020)
The endocrine disruptive effects caused by bisphenol A (BPA) are well known. Despite this, to date, evaluation of its long term effects is limited, meaning that there is still much to be unveiled in terms of alterations caused by perinatal exposure to BPA. Our aim was to determine if perinatal exposure to two different doses of BPA causes long term morphological and molecular alteration effects in the mammary gland (MG). We evaluated MG from Mongolian gerbil offspring exposed perinatally (during gestation and lactation) to 50 or 5000 μg/kg/day BPA. At 90 days of age the animals were subjected to a single dose of N-nitroso-N-methylurea in order to mimic a carcinogenic environment. At 6 months of age, animals in estrous were euthanized for morphological evaluation of the MGs. The MG architecture presented considerable changes in terms of detached epithelial cells, inflammation, glandular hyperplasia, and collagen fiber deposition. Furthermore, a higher index of epithelial cell proliferation was detected in comparison to the intact control group. In addition, we verified a higher molecular expression of EZH2 in the vehicle treated group, indicating that corn oil applied alone can alter the expression of this epigenetic biomarker. In conclusion, BPA perinatal exposure promotes significant changes in glandular cytoarchitecture and increases glandular epithelium proliferation rate, leading to the retention of stem-like properties. This event could compromise the fate and differentiation potential of mammary epithelium.
Keywords: BPA; Environment pollutant; Estrogen; EZH2; Morphologic alterations; Phospho-histone-h3